Coated aluminum-doped cobaltosic oxide material as well as preparation method and application thereof
By forming a pre-clad layer on the surface of aluminum-doped cobalt carbonate particles to form a tightly coated aluminum-doped cobalt tetroxide material, the problem of poor structural stability of lithium cobalt oxide at high voltage is solved, better cyclic stability and capacitance are achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202411815085.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-11
AI Technical Summary
Lithium cobalt oxide has poor structural stability at high voltage, resulting in fast capacity decay. The prior art has problems such as nanoadditive agglomeration, uneven mixing and high production costs.
A clad aluminum-doped tricobalt oxide material is used to form a pre-clad layer on the surface of aluminum-doped cobalt carbonate particles, including divalent metal ions and metal ions with valence state ≥3, to form a tight cladding layer to improve structural stability.
It realizes the improvement of the cyclic stability and capacitance of lithium cobalt oxide positive electrode material at high voltage, reduces production costs, and solves the problems of nano additive agglomeration and uneven mixing.
Smart Images

Figure CN119812242A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of high-voltage lithium cobalt oxide precursor materials, and in particular relates to a coated aluminum-doped cobalt oxide material and a preparation method and application thereof. Background Art
[0002] 3C consumer electronics products represented by smartphones have higher and higher requirements for battery life, which puts higher requirements on the volume energy density of positive electrode materials. The energy density of batteries is improved by increasing the working voltage of batteries. Lithium cobalt oxide is the dominant positive electrode material for 3C batteries. 4.53V lithium cobalt oxide will be gradually mass-produced, and higher voltage 4.55V lithium cobalt oxide is also in pre-research. As the cut-off voltage of lithium cobalt oxide increases, its specific capacity increases significantly. However, as the charging voltage increases, the structural stability of lithium cobalt oxide deteriorates, resulting in faster capacity decay. Doping can improve the structural stability of lithium cobalt oxide at high voltage. The existing high-voltage lithium cobalt oxide (LCO) technology is to pre-dope aluminum into the precursor cobalt oxide, use aluminum-doped cobalt oxide, lithium carbonate and additive coating materials (compounds of elements such as Mg, Ti, Zr) for solid phase mixing, and then calcined at high temperature. However, there are the following disadvantages: ⑴ The additive is a nanoparticle, which is easy to agglomerate. There is an uneven mixing problem when it is mixed with the precursor in the solid phase. During the sintering process of lithium cobalt oxide (LCO), a continuous and uniform protective layer cannot be formed on the surface of lithium cobalt oxide, and the side reactions on the surface of lithium cobalt oxide cannot be effectively inhibited, resulting in rapid decay of the cycle capacity; ⑵ The price of the raw materials of nano additives is high, resulting in high production costs.
[0003] In addition, high-voltage lithium cobalt oxide (LCO) technology is more dependent on the precursor cobalt tetroxide, and the mainstream precursor product is aluminum-doped cobalt tetroxide. The higher the voltage platform, the higher the aluminum doping amount. The aluminum doping amount of the 4.53V platform cobalt tetroxide reaches 9000ppm. Since aluminum is electrochemically inert, the development of higher voltage LCO by simply increasing the aluminum content by 10000ppm or more will reduce the capacity of the high-aluminum-doped LCO under the same voltage conditions. The prior art discloses that the core is doped with Mg and or transition metal (any one or a combination of at least two of Ni, Mn, Ti and Zr); the outer layer is doped with 7000-9000ppm of Al; the method used is wet coprecipitation under a carbonate system, but the aluminum in the outer layer is easy to precipitate and enrich. The prior art also discloses an aluminum-doped cobalt tetroxide core-shell material and a preparation method thereof, wherein the outer shell does not contain Al. Although the segregation problem of Al is solved, a variety of additives need to be added in the subsequent sintering process of lithium cobalt oxide. Summary of the invention
[0004] The purpose of the present application is to provide a coated aluminum-doped cobalt oxide material and its preparation method and application, aiming to solve the problem that the cycle stability of lithium cobalt oxide structure deteriorates and the capacity decays rapidly as the charging voltage increases.
[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0006] In a first aspect of the present application, a coated aluminum-doped cobalt tetroxide material is provided, comprising an inner core and a coating layer coating the inner core, wherein the inner core comprises aluminum-doped cobalt tetroxide, and the coating layer comprises an oxide containing metal ions, wherein the metal ions comprise divalent metal ions and metal ions with a valence state ≥3.
[0007] According to some embodiments of the coated aluminum-doped cobalt oxide material described in the present application, the doping amount of aluminum in the core is 4000ppm-9000ppm.
[0008] According to some embodiments of the coated aluminum-doped cobalt oxide material described in the present application, the diameter of the inner core is 15 μm-21 μm.
[0009] According to some embodiments of the coated aluminum-doped cobalt oxide material described in the present application, the chemical formula of the oxide is (1-x)MO·xNO z / 2 , M is the divalent metal ion, N is the metal ion with a valence ≥3, wherein 0.1≤X≤0.3, 3≤z≤6.
[0010] According to some embodiments of the coated aluminum-doped cobalt oxide material described in the present application, the divalent metal ions include Mg 2+ , Mn 2+ 、Ni 2+ 、Co 2+ One or more of; the metal ions with a valence of ≥3 include Ti 4+ 、Zr 4+ , Y 3+ ,La 3+ One or more of .
[0011] According to some embodiments of the coated aluminum-doped cobalt oxide material described in the present application, the thickness of the coating layer is 0.1 μm-2 μm.
[0012] In a second aspect of the present application, a method for preparing a coated aluminum-doped cobalt oxide material is provided, comprising the following steps:
[0013] The aluminum-doped cobalt carbonate particles, the divalent metal salt, the metal salt with a valence of ≥3 and the first precipitant are mixed to perform a precipitation reaction, so as to form a pre-coating layer on the surface of the aluminum-doped cobalt carbonate particles, and obtain a coated aluminum-doped cobalt carbonate containing the pre-coating layer;
[0014] The coated aluminum-doped cobalt carbonate is calcined to obtain a coated aluminum-doped cobalt tetroxide material.
[0015] According to some embodiments of the method for preparing a coated aluminum-doped cobalt oxide material described in the present application, the divalent metal salt includes Mg 2+ , Mn 2+ 、Ni 2+ 、Co 2+ One or more soluble sulfates, chlorides or nitrates of.
[0016] According to some embodiments of the method for preparing a coated aluminum-doped cobalt tetroxide material described in the present application, the metal salt with a valence of ≥3 includes Ti 4+ 、Zr 4+ , Y 3+ ,La 3+ One or more soluble sulfates, chlorides or nitrates of
[0017] According to some embodiments of the method for preparing a coated aluminum-doped cobalt oxide material described in the present application, the molar ratio of the divalent metal salt to the metal salt with a valence ≥3 is (2-8):1.
[0018] According to some embodiments of the method for preparing a coated aluminum-doped cobalt oxide material described in the present application, the mass ratio of the total amount of the divalent metal salt and the metal salt with a valence ≥ 3 to the first precipitant is (0.2-0.3):1.
[0019] According to some embodiments of the method for preparing a coated aluminum-doped cobalt oxide material described in the present application, the temperature of the coating reaction is 40°C-50°C.
[0020] According to some embodiments of the method for preparing a coated aluminum-doped cobalt oxide material described in the present application, the pH of the coating reaction is 7.0-8.5.
[0021] According to some embodiments of the method for preparing a coated aluminum-doped cobalt oxide material described in the present application, the reaction time of the coating reaction is 2h-6h.
[0022] According to some embodiments of the method for preparing a coated aluminum-doped cobalt oxide material described in the present application, the pre-coating layer is a hydrotalcite-like layer, and the chemical formula of the pre-coating layer is M is a divalent metal ion, N is a metal ion with a valence ≥ 3, wherein 0.1≤X≤0.3, and 0<n≤1.
[0023] According to some embodiments of the method for preparing a coated aluminum-doped cobalt tetroxide material described in the present application, the method for preparing aluminum-doped cobalt carbonate particles comprises the following steps:
[0024] The cobalt salt, the aluminum salt and the second precipitant are mixed to carry out a doping precipitation reaction to obtain aluminum-doped cobalt carbonate particles.
[0025] According to some embodiments of the method for preparing a coated aluminum-doped cobalt oxide material described in the present application, the first precipitant and the second precipitant each independently include one or more of ammonium bicarbonate, ammonium carbonate, sodium bicarbonate and sodium carbonate.
[0026] According to some embodiments of the method for preparing a coated aluminum-doped cobalt oxide material described in the present application, the cobalt salt includes one or more of cobalt sulfate, cobalt chloride, and cobalt nitrate.
[0027] According to some embodiments of the method for preparing a coated aluminum-doped cobalt oxide material described in the present application, the aluminum salt includes one or more of aluminum sulfate, aluminum chloride, and aluminum nitrate.
[0028] According to some embodiments of the method for preparing a coated aluminum-doped cobalt oxide material described in the present application, the mass ratio of the aluminum salt to the cobalt salt is (0.005-0.125):1.
[0029] According to some embodiments of the method for preparing a coated aluminum-doped cobalt oxide material described in the present application, the mass ratio of the cobalt salt to the second precipitant is (0.2-0.5):1.
[0030] The third aspect of the present application provides a lithium cobalt oxide positive electrode material, which is prepared from the coated aluminum-doped cobalt oxide material described in the first aspect of the present application or prepared from the coated aluminum-doped cobalt oxide material obtained by the preparation method described in the second aspect of the present application.
[0031] A fourth aspect of the present application provides a lithium battery, comprising the lithium cobalt oxide positive electrode material described in the third aspect of the present application.
[0032] Compared with the prior art, the beneficial effects of the present invention are:
[0033] 1. The core of the coated aluminum-doped cobalt tetroxide material described in the present application is aluminum-doped cobalt tetroxide, which is beneficial to improving the capacitance of the positive electrode material; the divalent metal ions contained in the coating layer are doped at the Li ion site, playing a similar role as a pillar, and the supporting structure is stable; the metal ions with a valence of ≥3 are doped at the Co ion site, which plays a role in alleviating lattice distortion and can improve the structural stability by forming a strong bond with the lattice oxygen. The synergistic effect of the outer layer coated divalent metal ions and high-valent metal ions is beneficial to improving the cycle stability performance of the positive electrode material, that is, the coated aluminum-doped cobalt tetroxide material described in the present application has better capacitance and cycle performance.
[0034] 2. The preparation method of the present invention comprises mixing aluminum-doped cobalt carbonate particles, divalent metal salts, metal salts with a valence of ≥3 and a first precipitant to carry out a coating reaction, thereby forming a pre-coating layer on the surface of the aluminum-doped cobalt carbonate particles. Since the pre-coating layer contains hydroxyl groups (OH-), the particles are tightly connected together through hydrogen bonds, and after calcination, a tightly coated aluminum-doped cobalt oxide is formed, thereby increasing its stability.
[0035] 3. The lithium cobalt oxide positive electrode material described in the present application includes the coated aluminum-doped cobalt oxide material described in the present application, so the lithium cobalt oxide positive electrode material has excellent cycle stability and capacity.
[0036] 4. The lithium battery described in the present application has excellent cycle stability and capacity because it includes the lithium cobalt oxide positive electrode material described in the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0038] Figure 1 This is a cross-sectional SEM image of the cobalt oxide material prepared in Example 1 of the present application;
[0039] Figure 2 This is the Ti element distribution diagram of the coating layer of the cobalt tetroxide material prepared in Example 1 of the present application by electron probe microscopy (EPMA);
[0040] Figure 3 This is a SEM image of the cobalt tetroxide material prepared in Example 2 of the present application;
[0041] Figure 4 This is the Zr element distribution diagram of the coating layer of the cobalt tetroxide material prepared in Example 2 of the present application by electron probe (EPMA);
[0042] Figure 5 This is a SEM image of the cobalt tetroxide material prepared in Example 4 of the present application;
[0043] Figure 6 This is a SEM image of the cobalt tetroxide material obtained in Comparative Example 1 of the present application;
[0044] Figure 7 The graphs are cycle performance test graphs of positive electrode materials prepared using the cobalt tetroxide materials prepared in Example 1 and Comparative Example 1 of the present application as raw materials. DETAILED DESCRIPTION
[0045] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0046] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0047] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0048] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0049] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0050] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0051] In a first aspect of an embodiment of the present application, a coated aluminum-doped cobalt tetroxide material is provided, comprising an inner core and a coating layer coating the inner core, wherein the inner core comprises aluminum-doped cobalt tetroxide, and the coating layer comprises an oxide containing metal ions, wherein the metal ions comprise divalent metal ions and metal ions with a valence state ≥3.
[0052] The core of the coated aluminum-doped cobalt tetroxide material in the embodiment of the present application is aluminum-doped cobalt tetroxide, which is beneficial to improving the capacitance of the positive electrode material; the divalent metal ions contained in the coating layer are doped at the Li ion site, playing a similar role as a pillar, and the supporting structure is stable; metal ions with a valence state ≥ 3 are doped at the Co ion site, which plays a role in alleviating lattice distortion and can improve structural stability by forming a strong bond with lattice oxygen. The synergistic effect of the outer layer coated divalent metal ions and high-valent metal ions is beneficial to improving the cycle stability of the positive electrode material, that is, the coated aluminum-doped cobalt tetroxide material provided in the embodiment of the present application has better capacitance and cycle performance.
[0053] In some embodiments of the present application, the amount of aluminum doped in the kernel is 4000ppm-9000ppm. The ppm here refers to a concentration of one part per million calculated by mass, which means that the mass of aluminum in aluminum-doped cobalt tetroxide accounts for 0.4%-0.9% of the total mass. As an example, the amount of aluminum doped in the kernel can be 4000ppm, 5000ppm, 6000ppm, 7000ppm, 8000ppm, 9000ppm, or any value between the above adjacent values. Selecting this amount of aluminum doping is beneficial to improving the structural stability of lithium cobalt oxide at high voltages of 4.53V and above, and increasing its capacitance.
[0054] In some embodiments of the present application, the diameter of the core is 15 μm-21 μm, such as 15 μm, 16 μm, 17 μm, 18 μm or 21 μm, or any value between the above adjacent values. This diameter range is conducive to improving the compaction density of the positive electrode material.
[0055] In some embodiments of the present application, the chemical formula of the oxide is (1-x)MO·xNO z / 2 , M is a divalent metal ion, N is a metal ion with a valence ≥ 3, wherein 0.1≤X≤0.3, 3≤z≤6. The valence value of N here corresponds to the value of z in the formula.
[0056] In some embodiments of the present application, the divalent metal ion is selected from Mg 2+ , Mn 2+ 、Ni 2+ 、Co 2+ One or more of; the metal ion with valence ≥ 3 is selected from Ti 4+ 、Zr 4+ , Y 3+ ,La 3+One or more of the above materials; the divalent metal ions and trivalent metal ions of the above materials can synergistically improve the stability of the positive electrode material. The divalent metal ions contained in the coating layer are doped at the Li ion site, playing a similar role as a pillar, and the supporting structure is stable; the metal ions with a valence of ≥3 are doped at the Co ion site, which can alleviate the lattice distortion and improve the structural stability by forming a strong bond with the lattice oxygen. The synergistic effect of the outer layer coated divalent metal ions and high-valent metal ions is conducive to improving the cycle stability of the positive electrode material.
[0057] In some embodiments of the present application, the thickness of the coating layer is 0.1 μm-2 μm, for example, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.8 μm, 1 μm, 1.5 μm or 2 μm, or any value between the above adjacent values. In some embodiments of the present application, the thickness of the coating layer is 0.1 μm-0.5 μm. If the thickness is less than 0.1 μm, the thickness of the coating layer cannot ensure the stability of the aluminum element in the kernel, which is not conducive to the capacity of the positive electrode material.
[0058] A second aspect of the embodiment of the present application provides a method for preparing a coated aluminum-doped cobalt oxide material, comprising the following steps:
[0059] S10: mixing aluminum-doped cobalt carbonate particles, a divalent metal salt, a metal salt with a valence of ≥3, and a first precipitant to perform a coating reaction, forming a pre-coating layer on the surface of the aluminum-doped cobalt carbonate particles, and obtaining a coated aluminum-doped cobalt carbonate containing the pre-coating layer;
[0060] S20: calcining the coated aluminum-doped cobalt carbonate to obtain a coated aluminum-doped cobalt tetroxide material.
[0061] The preparation method of the embodiment of the present invention mixes aluminum-doped cobalt carbonate particles, divalent metal salts, metal salts with a valence ≥ 3, and a first precipitant to perform a coating reaction, and forms a pre-coating layer on the surface of the aluminum-doped cobalt carbonate particles. Since the pre-coating layer contains hydroxyl groups (OH-), the particles are tightly connected together through hydrogen bonds, and after calcination, a tightly coated aluminum-doped cobalt tetroxide is formed, thereby increasing its stability.
[0062] [Step S10]
[0063] In some embodiments of the present application, the divalent metal salt includes Mg 2+ , Mn 2+ 、Ni 2+ 、Co 2+ One or more soluble sulfates, chlorides or nitrates of.
[0064] In some embodiments of the present application, the metal salt with a valence state ≥ 3 includes Ti 4+ 、Zr 4+ , Y 3+,La 3+ One or more soluble sulfates, chlorides or nitrates of
[0065] The divalent metal ions and trivalent metal ions selected from the above materials can synergistically improve the stability of the positive electrode material. The divalent metal ions contained in the coating layer are doped at the Li ion site, playing a similar role as a pillar, and the supporting structure is stable; the metal ions with a valence of ≥3 are doped at the Co ion site, which can alleviate the lattice distortion and improve the structural stability by forming a strong bond with the lattice oxygen. The synergistic effect of the outer layer coated divalent metal ions and high-valent metal ions is conducive to improving the cycle stability of the positive electrode material.
[0066] In some embodiments of the present application, the molar ratio of the divalent metal salt to the metal salt with a valence of ≥3 is (2-8):1, such as 2:1, 3:1, 3.6:1, 4.8:1, 5.7:1, 6.5:1, 7.3:1, 8:1, or any value between the above adjacent values. Selecting this ratio range is more conducive to the formation of a hydrotalcite-like substance (coating layer).
[0067] In some embodiments of the present application, the mass ratio of the total amount of the divalent metal salt and the metal salt with a valence state ≥ 3 to the first precipitant is (0.2-0.3):1, such as 0.2:1, 0.22:1, 0.25:1, 0.3:1, or any value between the above adjacent values. Selecting this range of values will make the metal ion precipitation more thorough and enable the precipitant to be fully utilized.
[0068] In some embodiments of the present application, the coating reaction temperature is 40°C-50°C, such as 40°C, 43°C, 45°C, 47°C, 48°C, 50°C, or any value between the above adjacent values. Within this temperature range, the precipitation reaction is stable and the hydrotalcite-like layer is more easily formed.
[0069] In some embodiments of the present application, the pH of the coating reaction is 7.0-8.5, for example, pH 7.0, pH 7.2, pH 7.5, pH 7.8, pH 8.0, pH 8.2, pH 8.3, pH 8.5, or any value between the above adjacent values. This pH range is conducive to the stable precipitation reaction and easier formation of a hydrotalcite-like layer.
[0070] In some embodiments of the present application, the reaction time of the coating reaction is 2h-6h, such as 2h, 3h, 4h, 5h, 6h, or any value between the above adjacent values. It is easier to form a hydrotalcite-like layer within this temperature and pH range.
[0071] In some embodiments of the present application, the pre-coating layer is a hydrotalcite-like layer, and the chemical formula of the pre-coating layer is , M is a divalent metal ion, N is a metal ion with a valence of ≥3, where 0.1≤X≤0.3, 0<n≤1. Hydrotalcite-like materials contain hydroxyl groups (OH-), and the particles are tightly connected by hydrogen bonds, forming a tightly coated aluminum-doped cobalt tetroxide after calcination. The formation of a coating layer on the precursor eliminates the need to add expensive nano-scale compounds in the preparation process of the rear-end lithium cobalt oxide positive electrode material, eliminates the problem of uneven solid phase mixing, simplifies the mixing process, reduces costs, and helps to improve the cycle performance of the rear-end positive electrode material.
[0072] In some embodiments of the present application, the method for preparing aluminum-doped cobalt carbonate particles includes the following steps: mixing a cobalt salt, an aluminum salt, and a second precipitant to perform a doping precipitation reaction to obtain aluminum-doped cobalt carbonate particles.
[0073] In some embodiments of the present application, the first precipitant and the second precipitant each independently include one or more of ammonium bicarbonate, ammonium carbonate, sodium bicarbonate and sodium carbonate; in some embodiments, the mass concentration of the first precipitant solution and the second precipitant solution are both 60g / L-220g / L, such as 60g / L, 70g / L, 80g / L, 90g / L, 110g / L, 120g / L, 128g / L, 156g / L, 187g / L, 220g / L, or any value between the above adjacent values. Selecting a precipitant within the above concentration range is conducive to maintaining the stability of the reaction and promoting a more complete reaction.
[0074] In some embodiments of the present application, the cobalt salt is selected from one or more of cobalt sulfate, cobalt chloride, and cobalt nitrate; the above cobalt salts are easily available from the market and can ensure a more stable reaction.
[0075] In some embodiments of the present application, the aluminum salt is selected from one or more of aluminum sulfate, aluminum chloride, and aluminum nitrate. The above aluminum salts are easily available from the market and can ensure a more stable reaction.
[0076] In some embodiments, the mass ratio of aluminum salt to cobalt salt is (0.005-0.125):1, such as 0.005:1, 0.008:1, 0.009:1, 0.101:1, 0.115:1, 0.125:1, or any value between the above adjacent values. This doping amount can ensure that the stability and capacitance of the obtained positive electrode material are better.
[0077] In some embodiments of the present application, the mass ratio of the cobalt salt to the second precipitant is (0.2-0.5):1, such as 0.2:1, 0.3:1, 0.4:1, 0.5:1, or any value between the above adjacent values. Selecting this mass ratio is conducive to the stable progress of the reaction.
[0078] In some embodiments of the present application, the doping precipitation reaction comprises the following steps:
[0079] First, a first doping reaction is performed at a reaction temperature of 30°C-40°C, such as 30°C, 32°C, 35°C, 40°C, and a pH of 7.0-8.5, such as pH 7.0, pH 7.3, pH 7.5, pH 8.0, and pH 8.5, until the particle size D50 of the aluminum-doped cobalt carbonate particles is 5.5 μm-6.5 μm; such as 5.5 μm, 5.8 μm, 6.0 μm, 6.1 μm, 6.2 μm, and 6.5 μm;
[0080] The selection of this reaction temperature is beneficial to ensuring the sphericity of the particles and the uniformity of aluminum doping. The pH range is beneficial to the growth of the particles, making the sphericity of the particles better.
[0081] Keeping the reaction temperature unchanged, adjust the pH to 6.5-7.5, for example, pH 6.5, pH 6.8, pH 7.0, pH 7.2, pH 7.5 to carry out the second doping reaction until the particle size D50 of the aluminum-doped cobalt carbonate particles grows to 19μm-22μm, for example, 19μm, 20μm, 20.5μm, 21μm, 21.6μm, 22μm. Adjusting the pH value is beneficial to accelerate the growth of the particles.
[0082] The aluminum-doped cobalt carbonate particles grow to a particle size of 19μm-22μm through a doping precipitation reaction. The volume of the aluminum-doped cobalt tetroxide particles formed after subsequent calcination treatment will be reduced, so that the diameter of the inner core of the finally obtained coated aluminum-doped cobalt tetroxide material is 15μm-21μm.
[0083] In some embodiments of the present application, the steps are also included: centrifugation, water washing and drying of the coated aluminum-doped cobalt carbonate in sequence; water washing is performed using hot water at 60°C-80°C, such as 60°C, 65°C, 68°C, 70°C, 75°C, 78°C, 80°C for 15min-25min, such as 15min, 18min, 20min, 22min, 25min. This temperature range has a good washing effect, can quickly clean the product, and the time is relatively short.
[0084] [Step S20]
[0085] In some embodiments of the present application, the calcination temperature is 700°C-850°C, such as 700°C, 720°C, 750°C, 780°C, 800°C, 820°C, 835°C, 850°C, etc., and can also be any value between the above adjacent values. The duration is 2h-5h; for example, 2h, 3h, 4h, 5h, and can also be any value between the above adjacent values. The calcination temperature range can form a relatively tight coating layer, and the surface of the particles is not easily damaged and it is not easy to produce micro powder.
[0086] In a third aspect of the embodiment of the present application, a lithium cobalt oxide positive electrode material is provided, which is prepared from the coated aluminum-doped cobalt oxide material of the first aspect of the present application or prepared from the coated aluminum-doped cobalt oxide material obtained by the preparation method of the second aspect of the present application. The lithium cobalt oxide positive electrode material of the present application includes the coated aluminum-doped cobalt oxide material of the present application, so that the lithium cobalt oxide positive electrode material has excellent cycle stability and capacity.
[0087] In a fourth aspect of the embodiment of the present application, a lithium battery is provided, comprising the lithium cobalt oxide positive electrode material of the third aspect of the present application. The lithium battery of the present application has excellent cycle stability and electric capacity because it comprises the lithium cobalt oxide positive electrode material of the present application.
[0088] Specific implementation cases:
[0089] Example 1
[0090] (1) Preparation of solution: dissolving and mixing soluble cobalt sulfate (cobalt salt) and aluminum sulfate crystals (aluminum salt), wherein the mass ratio of aluminum element to cobalt element is 0.0055, to obtain an aluminum-doped mixed solution with a cobalt salt mass concentration of 100 g / L;
[0091] Dissolve and mix two metal salts of soluble cobalt sulfate (divalent metal salt) and titanium sulfate (metal salt with a valence of ≥3) in a molar ratio of 3:1 to obtain a coating solution with a molar concentration of Co element of 1 mol / L;
[0092] The ammonium bicarbonate was dissolved to obtain an ammonium bicarbonate solution (the first precipitant and the second precipitant) with a mass concentration of 200 g / L.
[0093] (2) Synthesis of aluminum-doped cobalt carbonate core: water and ammonium bicarbonate solution are added as base liquids into a reaction kettle, and the aluminum-doped mixed solution and ammonium bicarbonate solution prepared in step (1) are added in a parallel feeding manner at a mass ratio of (0.16-0.25):1, the reaction temperature is controlled at 35±5°C, the pH value is 7.0-8.5 (the pH is controlled by adjusting the flow rate of the ammonium bicarbonate solution), and the reaction is carried out until aluminum-doped cobalt carbonate particles with a particle size D50 of 5.5 μm are obtained.
[0094] ⑶ Growth of the core of aluminum-doped cobalt carbonate: Continue to add the aluminum-doped mixed solution and ammonium bicarbonate solution prepared in step (1) in a mass ratio of (0.20-0.50):1 to the material of step (2), control the reaction temperature at 35±5°C, and the pH value at 6.5-7.5 (the pH is controlled by adjusting the flow rate of the ammonium bicarbonate solution). Intermittent growth is carried out in a cycle of stopping feeding after the reactor is full, standing, solid-liquid stratification, extracting the supernatant, and then continuing to feed. After extracting the supernatant, start stirring, and then turn on the feed pump. Continue to add the aluminum-doped mixed solution and ammonium bicarbonate solution in parallel, so that the aluminum-doped cobalt carbonate particles are grown to a particle size of 20μm after multiple growths.
[0095] (4) Coating of aluminum-doped cobalt carbonate: Add the coating solution prepared in step (1) and the ammonium bicarbonate solution in a mass ratio of (0.20-0.50):1 to the material obtained in step (3) in parallel, control the reaction temperature at 45±5°C, and the pH value at 7.0-8.0 (the pH is controlled by adjusting the flow rate of the ammonium bicarbonate solution). A pre-coating layer of cobalt-titanium hydrotalcite is deposited on the surface of the aluminum-doped cobalt carbonate particles to obtain a coated aluminum-doped cobalt carbonate slurry containing a pre-coating layer.
[0096] (5) Washing and drying: The coated aluminum-doped cobalt carbonate slurry obtained in step (4) is put into a centrifuge, washed with 60° C. hot water for 20 min, centrifuged and dehydrated, and then dried by a flash evaporator to obtain coated aluminum-doped cobalt carbonate particles containing a pre-coating layer.
[0097] (6) Calcination and decomposition: The coated aluminum-doped cobalt carbonate particles containing a pre-coating layer obtained in step (5) are subjected to high-temperature thermal decomposition at a temperature of 700° C. for 5 h to obtain a cobalt-titanium oxide-coated aluminum-doped cobalt oxide material.
[0098] The inner layer of the obtained product has an Al doping content of 4000ppm, a core diameter of 18μm, a coating thickness of 0.5μm, and a particle cross-section SEM image as shown below: Figure 1 The Ti element distribution diagram of the coating layer detected by electron probe is shown in Figure 2 As shown:
[0099] from Figure 1 It can be seen that the outer layer of the coated aluminum-doped cobalt tetroxide material prepared in Example 1 has a dense layer.
[0100] from Figure 2 It can be seen that the Ti element is evenly distributed in the coating layer of the coated aluminum-doped cobalt tetroxide material prepared in Example 1.
[0101] Example 2
[0102] (1) Preparation of solution: dissolving and mixing soluble cobalt chloride (cobalt salt) and aluminum chloride crystals (aluminum salt), wherein the mass ratio of aluminum element to cobalt element is 0.0083, to obtain an aluminum-doped mixed solution with a cobalt ion mass concentration of 120 g / L;
[0103] Dissolve and mix two metal salts, soluble cobalt chloride (divalent metal salt) and zirconium chloride (metal salt with a valence of ≥3) in a molar ratio of 6:1 to obtain a coating solution with a molar concentration of Co element of 1.5 mol / L;
[0104] The ammonium bicarbonate was dissolved to obtain an ammonium bicarbonate solution (the first precipitant and the second precipitant) with a mass concentration of 220 g / L.
[0105] (2) Synthesis of aluminum-doped cobalt carbonate core: water and ammonium bicarbonate solution are added as base liquids into a reaction kettle, and the aluminum-doped mixed solution and ammonium bicarbonate solution prepared in step (1) are added in a parallel feeding manner at a mass ratio of (0.16-0.25):1, the reaction temperature is controlled at 35±5°C, the pH value is 7.0-8.5 (the pH is controlled by adjusting the flow rate of the ammonium bicarbonate solution), and the reaction is carried out until aluminum-doped cobalt carbonate particles with a particle size D50 of 5.8 μm are obtained.
[0106] ⑶ Growth of the core of aluminum-doped cobalt carbonate: Continue to add the aluminum-doped mixed solution and ammonium bicarbonate solution prepared in step (1) in a mass ratio of (0.2-0.5):1 to the material of step (2), control the reaction temperature at 35±5°C, and the pH value at 6.5-7.5 (the pH is controlled by adjusting the flow rate of the ammonium bicarbonate solution). Intermittent growth is carried out in a cycle of stopping feeding after the reactor is full, standing, solid-liquid stratification, extracting the supernatant, and then continuing to feed. After extracting the supernatant, start stirring, and then turn on the feed pump. Continue to add the aluminum-doped mixed solution and ammonium bicarbonate solution in parallel, so that the aluminum-doped cobalt carbonate particles are grown to a particle size of 19μm after multiple growths.
[0107] (4) Coating of aluminum-doped cobalt carbonate: Add the coating solution prepared in step (1) and the ammonium bicarbonate solution in a mass ratio of (0.2-0.3):1 to the material obtained in step (3) in parallel, control the reaction temperature at 45±5°C, and the pH value at 7.0-8.0 (the pH is controlled by adjusting the flow rate of the ammonium bicarbonate solution). A pre-coating layer of cobalt-zirconium hydrotalcite is deposited on the surface of the aluminum-doped cobalt carbonate particles to obtain a coated aluminum-doped cobalt carbonate slurry containing a pre-coating layer.
[0108] (5) Washing and drying: The coated aluminum-doped cobalt carbonate slurry obtained in step (4) is put into a centrifuge, washed with 70° C. hot water for 20 min, centrifuged and dehydrated, and then dried by a flash evaporator to obtain coated aluminum-doped cobalt carbonate particles containing a pre-coating layer.
[0109] (6) Calcination and decomposition: The coated aluminum-doped cobalt carbonate particles containing a pre-coating layer obtained in step (5) are subjected to high-temperature thermal decomposition at a temperature of 760° C. for 3 h to obtain a cobalt-zirconium oxide-coated aluminum-doped cobalt oxide material.
[0110] The inner layer of the obtained product has an Al doping content of 6000ppm, a core diameter of 16μm, a coating thickness of 0.3μm, and a particle morphology SEM image as shown in Figure 3 The Zr element distribution of the coating layer detected by electron probe is shown in Figure 4 shown.
[0111] from Figure 3 It can be seen that the outer layer of the coated aluminum-doped cobalt tetroxide material prepared in Example 2 has a dense layer.
[0112] from Figure 4 It can be seen that the Zr element is evenly distributed in the coating layer of the coated aluminum-doped cobalt tetroxide material prepared in Example 2.
[0113] Example 3
[0114] (1) Preparation of solution: dissolve and mix soluble cobalt nitrate (cobalt salt) and aluminum nitrate crystals (aluminum salt), wherein the mass ratio of aluminum element to cobalt element is 0.0111, and obtain an aluminum-doped mixed solution with a mass concentration of cobalt salt of 110 g / L;
[0115] Dissolve and mix three metal salts of soluble magnesium nitrate (divalent metal salt), zirconium nitrate (metal salt with a valence of ≥3), and yttrium nitrate (metal salt with a valence of ≥3) in a molar ratio of 2:0.5:0.5 to obtain a coating solution with a molar concentration of Mg element of 1 mol / L;
[0116] The ammonium bicarbonate was dissolved to obtain an ammonium bicarbonate solution (the first precipitant and the second precipitant) with a mass concentration of 100 g / L.
[0117] (2) Synthesis of aluminum-doped cobalt carbonate core: water and ammonium bicarbonate solution are added as base liquids into a reaction kettle, and the aluminum-doped mixed solution and ammonium bicarbonate solution prepared in step (1) are added in a parallel feeding manner at a mass ratio of (0.16-0.25):1, the reaction temperature is controlled at 35±5°C, the pH value is 7.0-8.5 (the pH is controlled by adjusting the flow rate of the ammonium bicarbonate solution), and the reaction is carried out until an aluminum-doped cobalt carbonate core with a particle size D50 of 6.2 μm is obtained.
[0118] ⑶ Growth of the core of aluminum-doped cobalt carbonate: Continue to add the aluminum-doped mixed solution and ammonium bicarbonate solution prepared in step (1) in a mass ratio of (0.20-0.50):1 to the material of step (2), control the reaction temperature at 35±5°C, and the pH value at 6.5-7.5 (the pH is controlled by adjusting the flow rate of the ammonium bicarbonate solution). Intermittent growth is carried out in a cycle of stopping feeding after the reactor is full, standing, solid-liquid stratification, extracting the supernatant, and then continuing to feed. After extracting the supernatant, start stirring, and then turn on the feed pump. Continue to add the aluminum-doped mixed solution and ammonium bicarbonate solution in parallel, so that the aluminum-doped cobalt carbonate particles are grown to a particle size of 21μm after multiple growths.
[0119] (4) Coating of aluminum-doped cobalt carbonate: Add the coating solution prepared in step (1) and the ammonium bicarbonate solution in a mass ratio of (0.20-0.30):1 to the material obtained in step (3) in parallel, control the reaction temperature at 45±5°C, and the pH value at 7.0-8.0 (the pH is controlled by adjusting the flow rate of the ammonium bicarbonate solution). A pre-coating layer of magnesium zirconium yttrium hydrotalcite is deposited on the surface of the aluminum-doped cobalt carbonate particles to obtain a coated aluminum-doped cobalt carbonate slurry containing the pre-coating layer;
[0120] (5) Washing and drying: The coated aluminum-doped cobalt carbonate slurry obtained in step (4) is put into a centrifuge, washed with 80° C. hot water for 20 min, centrifuged and dehydrated, and then dried by a flash evaporator to obtain coated aluminum-doped cobalt carbonate particles containing a pre-coating layer.
[0121] (6) Calcination and decomposition: The coated aluminum-doped cobalt carbonate particles containing a pre-coating layer obtained in step (5) are subjected to high-temperature thermal decomposition at a temperature of 830° C. for 2 h to obtain a magnesium-zirconium-yttrium oxide-coated aluminum-doped cobalt oxide material.
[0122] The inner layer of the obtained product has an Al doping amount of 8000ppm, a core diameter of 17μm, and a coating thickness of 0.1μm. The product prepared in Example 3 was subjected to SEM and EPMA tests, and the results showed that the outer layer of the prepared coated aluminum-doped cobalt tetroxide material had a dense layer, and the coating layer contained Mg, Zr and Y elements.
[0123] Example 4
[0124] (1) Preparation of solution: dissolving and mixing soluble cobalt chloride (cobalt salt) and aluminum chloride crystals (aluminum salt), wherein the mass ratio of aluminum element to cobalt element is 0.0083, to obtain an aluminum-doped mixed solution with a cobalt salt mass concentration of 120 g / L;
[0125] Dissolve and mix soluble cobalt chloride (divalent metal salt) and soluble zirconium chloride (metal salt with a valence of ≥3) in a molar ratio of 6:1 to obtain a coating solution with a molar concentration of Co element of 1.5 mol / L;
[0126] The ammonium bicarbonate was dissolved to obtain an ammonium bicarbonate solution (the first precipitant and the second precipitant) with a mass concentration of 220 g / L.
[0127] (2) Synthesis of aluminum-doped cobalt carbonate core: water and ammonium bicarbonate solution are added as base liquids into a reaction kettle, and the aluminum-doped mixed solution and ammonium bicarbonate solution prepared in step (1) are added in a parallel feeding manner at a mass ratio of (0.16-0.25):1, the reaction temperature is controlled at 35±5°C, the pH value is 7.0-8.5 (the pH is controlled by adjusting the flow rate of the ammonium bicarbonate solution), and the reaction is carried out until aluminum-doped cobalt carbonate particles with a particle size D50 of 6.5 μm are obtained.
[0128] ⑶ Growth of the core of aluminum-doped cobalt carbonate: Continue to add the aluminum-doped mixed solution and ammonium bicarbonate solution prepared in step (1) in a mass ratio of (0.2-0.5):1 to the material of step (2), control the reaction temperature at 35±5°C, and the pH value at 6.5-7.5 (the pH is controlled by adjusting the flow rate of the ammonium bicarbonate solution). Intermittent growth is carried out in a cycle of stopping feeding after the reactor is full, standing, solid-liquid stratification, extracting the supernatant, and then continuing to feed. After extracting the supernatant, start stirring, and then turn on the feed pump. Continue to add the aluminum-doped mixed solution and ammonium bicarbonate solution in parallel, so that the aluminum-doped cobalt carbonate particles are grown to a particle size of 22μm after multiple growths.
[0129] (4) Coating of aluminum-doped cobalt carbonate: Add the coating solution prepared in step (1) and the ammonium bicarbonate solution in a mass ratio of (0.2-0.5):1 to the material obtained in step (3) in parallel, control the reaction temperature at 35±5°C, and the pH value at 6.5-7.5. A pre-coating layer with a thickness of 0.3 μm is deposited on the surface of the aluminum-doped cobalt carbonate particles to obtain a coated aluminum-doped cobalt carbonate slurry containing a pre-coating layer.
[0130] (5) Washing and drying: The coated aluminum-doped cobalt carbonate slurry obtained in step (4) is put into a centrifuge, washed with 70° C. hot water for 20 min, centrifuged and dehydrated, and then dried by a flash evaporator to obtain coated aluminum-doped cobalt carbonate particles containing a pre-coating layer.
[0131] (6) Calcination and decomposition: The coated aluminum-doped cobalt carbonate particles containing a pre-coating layer obtained in step (5) are subjected to high-temperature thermal decomposition at a temperature of 760°C for 3 hours to obtain a cobalt-zirconium oxide-coated aluminum-doped cobalt oxide material, wherein the core diameter is 18 μm.
[0132] The SEM image of the cobalt tetroxide material prepared in Example 4 is as follows Figure 5 As shown:
[0133] from Figure 5 It can be seen that the coating layer of the coated aluminum-doped cobalt tetroxide material prepared in Example 4 is not strongly bonded, and the surface layer is broken to produce a large amount of fine powder.
[0134] Example 5
[0135] The only difference between Example 5 and Example 1 is that the coating solution in Example 5 is prepared by dissolving and mixing two metal salts of soluble cobalt sulfate (divalent metal salt) and titanium sulfate (metal salt with a valence ≥ 3) in a molar ratio of 10:1.
[0136] The product prepared in Example 5 was subjected to SEM detection, and the results showed that the coating layer of the prepared coated aluminum-doped cobalt tetroxide material was not strongly bonded, and there was a large amount of fine powder on the surface.
[0137] Comparative Example 1
[0138] The difference between Comparative Example 1 and Example 1 is that after the synthesis of aluminum-doped cobalt carbonate is completed, no coating treatment is performed, that is, step (4) in Example 1 is omitted, and the rest is the same as Example 1.
[0139] Specifically:
[0140] (1) Preparation of solution: dissolving and mixing soluble cobalt sulfate (cobalt salt) and aluminum sulfate crystals (aluminum salt), wherein the mass ratio of aluminum element to cobalt element is 0.0055, to obtain an aluminum-doped mixed solution with a cobalt salt mass concentration of 100 g / L;
[0141] The ammonium bicarbonate was dissolved to obtain an ammonium bicarbonate solution (the first precipitant and the second precipitant) with a mass concentration of 200 g / L.
[0142] (2) Synthesis of aluminum-doped cobalt carbonate core: water and ammonium bicarbonate solution are added as base liquids into a reaction kettle, and the aluminum-doped mixed solution and ammonium bicarbonate solution prepared in step (1) are added in a parallel feeding manner at a mass ratio of (0.16-0.25):1, the reaction temperature is controlled at 35±5° C., the pH value is 7.0-8.5 (the pH is controlled by adjusting the flow rate of the ammonium bicarbonate solution), and the reaction is carried out until aluminum-doped cobalt carbonate particles with a particle size D50 of 6.0 μm are obtained;
[0143] ⑶ Growth of the core of aluminum-doped cobalt carbonate: Continue to add the aluminum-doped mixed solution and ammonium bicarbonate solution prepared in step (1) in a mass ratio of (0.20-0.50):1 to the material of step (2), control the reaction temperature at 35±5°C, and the pH value at 6.5-7.5 (the pH is controlled by adjusting the flow rate of the ammonium bicarbonate solution). Intermittent growth is carried out in a cycle of stopping feeding after the reactor is full, standing, solid-liquid stratification, extracting the supernatant, and then continuing to feed. After extracting the supernatant, start stirring, and then turn on the feed pump. Continue to add the aluminum-doped mixed solution and ammonium bicarbonate solution in parallel, so that the aluminum-doped cobalt carbonate particles are grown to a particle size of 21μm after multiple growths.
[0144] (4) Washing and drying: The aluminum-doped cobalt carbonate slurry obtained in step (3) is put into a centrifuge, washed with 60° C. hot water for 20 min, centrifuged and dehydrated, and then dried by a flash evaporator to obtain aluminum-doped cobalt carbonate particles.
[0145] (5) Calcination and decomposition: The aluminum-doped cobalt carbonate particles obtained in step (4) are subjected to high-temperature thermal decomposition at a temperature of 700° C. to obtain aluminum-doped cobalt tetroxide with an Al content of 4000 ppm.
[0146] The SEM image of the obtained product is shown in Figure 6 As shown, from Figure 6It can be seen that Al is precipitated in the inner layer of the material prepared in Comparative Example 1, and is enriched in the outer layer of the particles in a flake shape.
[0147] The aluminum-doped cobalt oxide prepared in Comparative Example 1 and the coated aluminum-doped cobalt oxide prepared in Example 1 were used to prepare lithium cobalt oxide positive electrode materials. The cycle performance of the obtained lithium cobalt oxide positive electrode materials at a high voltage of 4.60 V is as follows: Figure 7 As shown:
[0148] from Figure 7 It can be seen that the positive electrode material obtained by using the coated aluminum-doped cobalt tetroxide prepared in Example 1 of the present application as raw material has better cycle performance at a high voltage of 4.60V, that is, the positive electrode material obtained by using the coated aluminum-doped cobalt tetroxide prepared in Example 1 of the present application as raw material has better electrochemical performance.
[0149] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A coated aluminum-doped cobalt oxide material, characterized in that: The invention comprises a core and a coating layer covering the core, wherein the core comprises aluminum-doped cobalt tetroxide, and the coating layer comprises an oxide containing metal ions, wherein the metal ions comprise divalent metal ions and metal ions with a valence state of ≥3.
2. The coated aluminum-doped cobalt oxide material according to claim 1, characterized in that: The doping amount of aluminum in the core is 4000ppm-9000ppm; And / or, the diameter of the core is 15 μm-21 μm; And / or, the chemical formula of the oxide is (1-x)MO·xNO z / 2 , M is the divalent metal ion, N is the metal ion with a valence ≥3, wherein 0.1≤X≤0.3, 3≤z≤6.
3. The coated aluminum-doped cobalt oxide material according to claim 1 or 2, characterized in that: The divalent metal ions include Mg 2+ , Mn 2+ 、Ni 2+ 、Co 2+ One or more of; The metal ions with a valence of ≥3 include Ti 4+ 、Zr 4+ , Y 3+ ,La 3+ One or more of; And / or, the coating layer has a thickness of 0.1 μm-2 μm.
4. A method for preparing a coated aluminum-doped cobalt oxide material, characterized in that: The following steps are involved: The aluminum-doped cobalt carbonate particles, the divalent metal salt, the metal salt with a valence of ≥3 and the first precipitant are mixed to perform a coating reaction, so as to form a pre-coating layer on the surface of the aluminum-doped cobalt carbonate particles, and obtain a coated aluminum-doped cobalt carbonate containing the pre-coating layer; The coated aluminum-doped cobalt carbonate is calcined to obtain a coated aluminum-doped cobalt tetroxide material.
5. The method for preparing a coated aluminum-doped cobalt oxide material according to claim 4, characterized in that: The divalent metal salt includes Mg 2+ , Mn 2+ 、Ni 2+ 、Co 2+ Soluble sulfates, chlorides or nitrates of one or more of And / or, the metal salt with a valence state ≥ 3 includes Ti 4+ 、Zr 4+ , Y 3+ ,La 3+ one or more soluble sulfates, chlorides or nitrates of and / or, the molar ratio of the divalent metal salt to the metal salt with a valence ≥ 3 is (2-8):1; And / or, the mass ratio of the total amount of the divalent metal salt and the metal salt with a valence ≥ 3 to the first precipitant is (0.2-0.3):
1.
6. The method for preparing a coated aluminum-doped cobalt oxide material according to claim 4, characterized in that: The coating reaction temperature is 40°C-50°C; And / or, the pH of the coating reaction is 7.0-8.5; And / or, the reaction time of the coating reaction is 2h-6h; And / or, the pre-coating layer is a hydrotalcite-like layer, and the chemical formula of the pre-coating layer is M is a divalent metal ion, N is a metal ion with a valence ≥ 3, wherein 0.1≤X≤0.3, and 0<n≤1.
7. A method for preparing a coated aluminum-doped cobalt oxide material according to any one of claims 4 to 6, characterized in that: The preparation method of the aluminum-doped cobalt carbonate particles comprises the following steps: The cobalt salt, the aluminum salt and the second precipitant are mixed to carry out a doping precipitation reaction to obtain aluminum-doped cobalt carbonate particles.
8. The method for preparing a coated aluminum-doped cobalt oxide material according to claim 7, characterized in that: The first precipitant and the second precipitant each independently include one or more of ammonium bicarbonate, ammonium carbonate, sodium bicarbonate and sodium carbonate; And / or, the cobalt salt includes one or more of cobalt sulfate, cobalt chloride, and cobalt nitrate; And / or, the aluminum salt includes one or more of aluminum sulfate, aluminum chloride, and aluminum nitrate; And / or, the mass ratio of the aluminum salt to the cobalt salt is (0.005-0.125):1; And / or, the mass ratio of the cobalt salt to the second precipitant is (0.2-0.5):
1.
9. A lithium cobalt oxide positive electrode material, characterized in that: The invention is prepared from the coated aluminum-doped cobalt oxide material according to any one of claims 1 to 3 or prepared from the coated aluminum-doped cobalt oxide material obtained by the preparation method according to any one of claims 4 to 8.
10. A lithium battery, characterized in that: Including the lithium cobalt oxide positive electrode material as described in claim 9.
Citation Information
Cited By
Composite cobaltosic oxide precursor material and preparation method and application thereof
CN120565666A